Tata Letak dan Penerangan Lampu Tenaga Surya Pada Panti Kemah Peduli Sahabat Kasih - Hidayat, Trifenaus Prabu; Sugioko, Andre; Widiarto, Sandra Octaviani B.; Nur, Tajuddin (Jurnal Pengabdian Masyarakat Charitas, 2024)
Kemah Peduli Sahabat Kasih is a shelter for ODGJ (people with mental disorders) managed by one family. This shelter is located at Jl. Kp. Cicayur Kebun Manggu No.21, RW.1, Cisauk, Tangerang, Banten. In its operational activities, this shelter does not yet have adequate lighting. One of the facilities, precisely on the access road to the shelter, is inadequate. In addition, the lighting facilities in the front and back yards are also inadequate. Therefore, the purpose of creating lighting facilities on the access road to the shelter is to make it easier to get to the shelter, especially to provide lighting around the shelter so that nighttime operational activities are not hampered. The existence of lighting facilities on the access road to the shelter and lighting in the front and back yards is one of the important things to ensure security and safety in supporting nighttime operational activities safely and comfortably. The community service activity of utilizing solar energy in public street lighting as a replacement for conventional energy in Cisauk has gone well. This is supported by the results of the trial of the lights being able to be turned on and off, and the results of the interview gave a good activity score.